Characteristics of the Clinical Course of Autochthonous Hepatitis E in the Central Region of Russia - E. Yu. Malinnikova; V. G. Koptyug; M. I. Mikhailov (Журнал инфектологии)
The records of total 123 patients with hepatitis E on treatment in the infectious diseases hospital in the city of Belgorod were reviewed. Diagnosis – «acute hepatitis E» was based on the generally accepted criteria: biochemical analysis, etiological interpretation (identification of antibodies to hepatitis E of the IgM and IgG, HEV RNA with the exception of the etiologic role of other hepatotropic viruses, including Epstein-Barr virus and cytomegalovirus). HEV RNA was determined by PCR, genotyping was performed by standard methods based on the results of sequencing. The study of clinical manifestations in patients with acute hepatitis E allowed to establish some specific features of hepatitis E: predominantly occurrence in adults at the age 30 years and more; frequent complaints of arthralgia in the prejaundice period, the lack of improvement after jaundice development; pronounced dyspeptic symptoms and long bilirubinemia combined with mild transaminase elevation, hepatomegaly with no concomitant increase in the spleen. The data on the fulminant forms of hepatitis E are presented. Herein we describe the case of fulminant course of infection with a fatal outcome. Analysis of cases of severe hepatitis E have revealed the following risk factors: heart disease, chronic biliary disease, obesity, diabetes mellitus, chronic alcohol intoxication. The analysis of specific clinical manifestations of this infection is needed to select the right strategy of patient following, to set integrated differential diagnostic approach in the management of patients with middle and old age with the presence of jaundice and patients with hepatitis of unknown etiology. The inclusion of hepatitis E markers to the diagnostic algorithm is necessary for such patients.